PENGARUH PENGGUNAAN PENDEKATAN CONTEXTUAL TEACHING LEARNING TERHADAP PRESTASI BELAJAR IPA PADA SISWA KELAS V SD NEGERI KARANGTAWANG 02 CILACAP - Hernadia Asinda Afriani; Veator Renyaan (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2018)
Abstrack: The purpose of this research is to know the influence of contextual teaching learning approach to learning achievement of IPA in SDN Karangtawang 02 Cilacap Lesson Year 2017/2018. The research is an experimental research with Experiment Quasi type Noquivalent Control Group type. Data collection techniques in this study include documentation techniques and test techniques. The result of descriptive research showed that the average score of science achievement that was taught by using Contextual Teaching and Learning (CTL) approach was 20,000 included in high category and the average score of science achievement taught with the conventional approach was 14,176 included in medium category. In t-test obtained tcount = 2.954 with p = 0.006 which means the hypothesis accepted and very significant.